A study into the clinicopathological profile of patients with voice change - A. B., Baneesh; T., Dhanya; A., Jinsha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Hoarseness is a symptom used to describe change in normal quality of voice and is usually described as harsh, grating voice which can be lower in pitch and more or less discordant. Methods: The present study was carried out on 160 patients in the Department of ENT in PKDIMS over a period of 2 years from 2018 March to 2020 March. All patients with a history of voice change were evaluated. Results: 160 patients between the age group of 21- 80 years were studied. The number of males and females were 97 (61%) and 63 (39%) respectively. Laborers (32%) and housewives (21%) are the major group affected. Smoking (25%) was the most common predisposing factor followed by alcohol consumption (21%). Voice change can be due to various pathologies. In the present study the most common etiology for voice change was vocal nodules (23%) followed by chronic laryngitis (13%), growth in the pharynx and larynx (11%). Conclusions: Voice is important for our communication. Any disturbance in voice affects the individual’s social and personal life. Treatment depends on the individuals needs and their diagnosis. Drug therapy, voice therapy, microlaryngeal surgery are the various treatment modalities done for our patients.